2003
DOI: 10.1590/s0100-40422003000400003
|View full text |Cite
|
Sign up to set email alerts
|

Flavonóides glicosilados das folhas e flores de Bauhinia forficata (Leguminosae)

Abstract: Recebido em 5/4/02; aceito em 6/2/03 FLAVONOIDS GLYCOSIDES FROM LEAVES AND FLOWERS OF Bauhinia forficata (LEGUMINOSAE). From the leaves of Bauhinia forficata kaempferol and four flavonoid glycosides, 3,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 5 publications
(7 reference statements)
5
36
0
12
Order By: Relevance
“…and m/z 287 (aglycone) in the MS (relative abundance proportions: 27:39:100, respectively). 1 H and 13 C NMR (400 MHz and 100 MHz respectively, DMSO-d 6 /drops D 2 O) analyses with the help of the correlation on the COSY, HMQC and HMBC spectra and comparison of their spectral data with those already reported, 20,21 confirmed the structure of kaempferol-3,7-O-(α)-dirhamnoside (kaempferitrin) (Figure 1) for this compound.…”
Section: Resultssupporting
confidence: 63%
“…and m/z 287 (aglycone) in the MS (relative abundance proportions: 27:39:100, respectively). 1 H and 13 C NMR (400 MHz and 100 MHz respectively, DMSO-d 6 /drops D 2 O) analyses with the help of the correlation on the COSY, HMQC and HMBC spectra and comparison of their spectral data with those already reported, 20,21 confirmed the structure of kaempferol-3,7-O-(α)-dirhamnoside (kaempferitrin) (Figure 1) for this compound.…”
Section: Resultssupporting
confidence: 63%
“…The IR spectrum displayed O-H stretching bands at 3350 cm -1 for 4 and 3375 cm -1 for 5, and conjugated carbonyl group absorptions at 1675 cm -1 and 1667 cm -1 , respectively. The 1 H NMR spectra of compounds 4 and 5 showed two meta-coupled doublets for A-ring, at δ H 6.55 (d, J=2.2 Hz, H-6), 6.13 (d, J=2.2 Hz, H-8) for 4 and 6.35 (d, J=2.0 Hz, H-6), 6.44 (d, J=2.0 Hz, H-8) for 5 and two orto-coupled doublets, for B-ring, at δ H 8.02 (d, J=8.8 Hz, H-2'/6') and 6.99 (d, J=8.8 Hz, H-3'/5') for 4 and 8.08 (d, J=7.9 Hz, H-2'/6'), 7.02 (d, J=7.8 Hz, H-3'/5') for 5, commonly observed in the kaempferol nucleus (Pizzolatti et al, 2003). Also, one signal for a chelated hydroxyl (OH-5) was observed at δ H 12.76 for 4 and 12.53 for 5.…”
Section: Resultsmentioning
confidence: 94%
“…The signals in C 158.66 and C 135.63 were attributed, after comparison with literature (Pizzolatti et al, 2003;Rastrelli et al, 1995), to the carbons C-2 and C-3 respectively, fact that strengthened the suggestion of 1 being a fl avone. ' .…”
Section: Structure Determination Ofmentioning
confidence: 54%
“…The characterization and the location of the diglucoside unit (rutinoside) in C-3 was based on the following observations: a) the chemical shift of C-2 ( C 158.99), revealed by the 13 C NMR spectrum, suggested the presence of glycoside in C-3; b) the long-distance correlation between the glucose anomeric hydrogen H-1 '' ( H 5.23,d,J=7.8 Hz) and the carbon C-3 ( C 133.53; 3 J CH ), observed in the HMBC spectrum, permitted to defi ne the bond -O rutinoside; c) the chemical shift of the glucose methylene carbon ( C 67.56) permitted the location of the rhamnose unit in this carbon atom, since the signal of hydroxymethylene group free of a glycoside unit appears around C 62.12 (Pizzolatti et al, 2003); d) the HMBC spectrum revealed the correlation between the rhamnose anomeric hydrogen H-1 ''' ( H 4.54, d, J=1.1) and the glucose methylene carbon C-6 '' . Through the two-bond correlations ( 2 J CH ) of H-6 ( H 6.21) with C-7 ( C 166.51) and H-6 ( H 6.21) with C-5 ( C 163.15) it was possible to determine that C-5 and C-7 sustain hydroxyl.…”
Section: Structure Determination Ofmentioning
confidence: 99%